LATAR ALAM GEOMORFOLOGIS PERISTIWA PERANG GERILYA JENDERAL BESAR SUDIRMAN (1948-1949) - Yulian Saputra; Muhammad Azmi (Jurusan Pendidikan Ilmu Pengetahuan Sosial FKIP Universitas Mulawarman, 2021)
This study describes the geomorphological natural setting that became the guerrilla event of General Sudirman through literature studies, concepts, theories, and relevant previous research results. The study area of this research covers the central and southern zones of Java Island. The research analysis used descriptive analysis with the help of satellite image interpretation. This study indicates that the guerrilla route covers a geomorphological area that stretches across three provinces in Java Island. The geomorphological background is the karst landscape of Gunung Kidul and the volcanic slopes of Mount Wilis.